Wave and its formal and chromatic representations in fashion fabric designs (Al-Academy, 2026)
Wave is a dynamic work that includes compositional and structural effects of colors, shapes and lighting effects that stimulate visual vision with dramatic energy influenced by instantaneous generative impulses. It can be said that a shape wavers with another shape and color wavers with another color in a way characterized by aesthetic kinetic energy, such that we see that color and shape achieve a vision that is consistent with the wave vibrations emitted by the visual energy emanating from a sensory vision in which color and shape are integrated and become a bright wave on the design space ,The research included three chapters. The first chapter dealt with the research problem, its importance, its objective, and its limits. The research problem focused on the subject of wavying and its formal and chromatic representations because it is a new subject that deserves attention and research. The importance of the research included that it may add to researchers and students’ knowledge of the subject of wavying, as the research aims to identify wavying and its formal and chromatic representations in fashion fabric designs. The theoretical framework included two topics. The first topic focused on the concept of wavying, while the second topic focused on the formal and chromatic representations of wavying in fashion fabric designs. As for the research procedures, a number of fashions by the Italian designer Emilio Pucci were selected and analyzed. From here, the most important results were reached, including that wavying has achieved innovative results through